Joint Angle and Frequency Estimation Using Multiple-Delay Output Based on ESPRIT. (28th December 2010) - Xudong Xudong, Wang Wang
Abstract : This paper presents a novel ESPRIT algorithm-based joint angle and frequency estimation using multiple-delay output (MDJAFE). The algorithm can estimate the joint angles and frequencies, since the use of multiple output makes the estimation accuracy greatly improved when compared with a conventional algorithm. The useful behavior of the proposed algorithm is verified by simulations.